Assessment of influence of a regular physical activity on physical condition and bone density in women aged 50–60 - Ćwirlej-Sozańska, Agnieszka (European Journal of Clinical and Experimental Medicine, 2015)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Objectives: The aim of the study was to assess the influence of regular physical activity on bone density in women aged 50-60. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods: As research tools, a standardized questionnaire designed by the authors with particulars and data concerning participants’ lifestyle as well as Seven-Day Physical Activity Recall were applied. Research equipment was used to measure mineral density of bones - densitometry of the lumbar spine and femoral neck by means of dual energy X-ray absorptiometry (DEXA). Additionally, Eurofit for Adults, a physical fitness test was conducted. Participants: The study included 117 postmenopausal women aged 50–60. Inclusion criteria were female gender, systematic physical activity in form of general fitness activities 2–3 times a week for at least 5 years. The test group consisted of 60 women. The control group included 57 women living sedentary lifestyle. All subjects were the residents of Rzeszów. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results: On the basis of the tests conducted it was found that bone density in the active women (the test group) was higher in comparison with the inactive women (the control group). There was low correlation between bone density and the amount of time dedicated to physical activity per week. There was no correlation between bone density and the duration of exercise (in years). Moreover, substantially higher level of physical capacity was found in the test group than in the control group. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions: Conducted research proved that systematic moderate physical activity affects favourably higher level of physical capacity and higher level of mineral bone density in women after 50 years of age.